Design, synthesis, and characterization of solution processable photoresponsive polythiophenes - Meilianty Gunawan. (2010)
A series of regiorandom and regioregular azobenzene-functionalized polythiophene derivatives was prepared. The polymerization was done via oxidative polymerization to produce regiorandom polymers. A new strategy to produce a novel regioregular azobenzene-substituted polythiophene via post polymerization functionalization has been developed and thoroughly discussed. The solubility issue which was the main issue in most azobenzene-containing polythiophene systems has been solved by the incorporation of butyl and trifluoromethyl functional groups at the para position of the azobenzene. Polymers with different alkyl spacer lengths (i.e. butyl vs octyl) were also synthesized and studied. The structural dependence of UV-Vis absorption, photoluminescence, electrochemical parameters, and film morphology of these polymer series was systematically studied. It was observed that a competitive force between the H-aggregation in azobenzene side chains and lamella packing in conjugated polythiophene backbone existed. This competition depended on different substitutents at the para position of azobenzene, backbone regioregularity, and alkyl spacer length between azobenzene and polythiophene backbone. Other findings also showed that a photoluminescence quenching occurred due to charge transfer from polythiophene backbone to cis azobenzene upon UV irradiation, a phenomenon which was further evidenced by cis → trans sensitization process during back isomerization.